An Estimation of Lifetime Fatal Carcinogenesis Risk Attributable to Radiation Exposure in the First Year Following Polytrauma: A Major Trauma Center's Experience Over 10 Years. (7th August 2019) - Howard, Anthony; West, Robert; Iball, Gareth; Panteli, Michalis; Pandit, Hemant; Giannoudis, Peter V.
Abstract : Background: The utilization of medical imaging continues to rise, including routine use in major trauma centers. The aims of this study were to estimate the amount of radiation exposure from radiographic imaging and the associated fatal carcinogenesis risk among patients treated for polytrauma at 1 institution. Methods: Included were patients who were admitted to our institution with an Injury Severity Score (ISS) of ≥16 during the period of January 2007 to December 2016. Records of patients were reviewed to assess exposures to radiation (excluding fluoroscopy) in the 12 months following injury. The risk of developing a fatal cancer of any type was modeled using patient age and sex, on the basis of the International Commission on Radiological Protection (ICRP) recommendations. Estimates of cancer risk were based on the exposure received and then imported into previously developed models. Results: Overall, 2, 394 patients, with a mean ISS of 28.66 (range, 17 to 66), were included in our analysis. The mean total radiation dose received was 30.45 mSv and the median dose was 18.46 mSv. One hundred and fifteen patients (4.8% of the cohort) received ≥100 mSv of radiation. The total patient group had a 3.56% mean risk of fatal carcinogenesis of any type that related solely to medical exposure of radiation as a result of their injuries. In their lifetime, 85 patients would be expected to develop cancer as a result of medical imaging that they had undergone in the year following their accident. The ISS and the body region of injury contributing to the ISS were predictive of the level of radiation exposure. Conclusions: Those involved in trauma care can use the ISS and body region to predict radiation exposure and the risk of fatal carcinogenesis of any type. We found that, for injuries to the limb and pelvis, the greater the severity of injury, the greater the radiation exposure and fatal carcinogenesis risk. However, this study does not provide an actuarial analysis. It is unknown how many patients in the study went on to develop cancer. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.